EFEKTIVITASPEMBEBASAN BERSYARATDAN CUTI MENJELANG BEBASSERTA CUTI BERSYARAT BAGI WARGA BINAAN DALAM UPAYA MENGATASI OVER CAPACITY DI LAPAS KLAS II A PADANG - Darwan, Darwan; Fahmiron, Fahmiron (UNES Journal of Swara Justisia, 2017)
The pattern of guidance in the penal system based on UU No. 12 Tahun 1995 concerning Pemasyarakatan is done gradually until the efforts of integrating prisoners and prisoners to the community through conditional free program in the form of Conditional Liberal (PB), Free Before Leave (CMB) and Conditional Leave (CB). To see the implications of this matter, it can be seen directly about the effectiveness of the program free of conditional in Prisons in its implementation in Lapas Klas IIA Padang which has over 200% capacity over the existing capacity. This study uses primary data as the main data obtained from interviews, supporting data is secondary data obtained from the results of literature research/document studies. Based on the result of the research, it is found that the procedure of Conditional Free Program implementation at Lapas Klas IIA Padang based on the provision of Human Rights Permenkum No. 21 Tahun 2013 which was amended by Permenkum HAM No. 21 Tahun 2016. Referring to the rule of Lapas Klas IIA Padang runs a conditional free program with administrative governance system in Lapas Klas IIA Padang intended to streamline and optimize the implementation of the program free of conditional, so it can be seen the effectiveness of the implementation of the program in overcoming the advantages Capacity at Lapas Klas IIA Padang based on percentage comparison parameters between the number of increase in the implementation of the program free of conditional with the percentage increase in the number of homes in Lapas Klas IIA Padang. The implementation of a parole program at Lapas IIA Padang faces several obstacles including obstacles in the legal administration system, constraints from prisoners and prisoners and the obstacles posed by legal rules that provide tightening on the implementation of the free program as regulated in PP Nomor 99 Tahun 2012.